Histone Methyltransferase G9a Is Required for Cardiomyocyte Homeostasis and Hypertrophy. Issue 13 (26th September 2017) - Papait, Roberto; Serio, Simone; Pagiatakis, Christina; Rusconi, Francesca; Carullo, Pierluigi; Mazzola, Marta; Salvarani, Nicolò; Miragoli, Michele; Condorelli, Gianluigi
Abstract : Background: Correct gene expression programming of the cardiomyocyte underlies the normal functioning of the heart. Alterations to this can lead to the loss of cardiac homeostasis, triggering heart dysfunction. Although the role of some histone methyltransferases in establishing the transcriptional program of postnatal cardiomyocytes during heart development has been shown, the function of this class of epigenetic enzymes is largely unexplored in the adult heart. In this study, we investigated the role of G9a/Ehmt2, a histone methyltransferase that defines a repressive epigenetic signature, in defining the transcriptional program for cardiomyocyte homeostasis and cardiac hypertrophy. Methods: We investigated the function of G9a in normal and stressed cardiomyocytes with the use of a conditional, cardiac-specific G9a knockout mouse, a specific G9a inhibitor, and high-throughput approaches for the study of the epigenome (chromatin immunoprecipitation sequencing) and transcriptome (RNA sequencing); traditional methods were used to assess cardiac function and cardiovascular disease. Results: We found that G9a is required for cardiomyocyte homeostasis in the adult heart by mediating the repression of key genes regulating cardiomyocyte function via dimethylation of H3 lysine 9 and interaction with enhancer of zeste homolog 2, the catalytic subunit of polycomb repressive complex 2, and MEF2C-dependent gene expression by forming a complex with this transcription factor. The G9a-MEF2C complex was found to be required also for the maintenance of heterochromatin needed for the silencing of developmental genes in the adult heart. Moreover, G9a promoted cardiac hypertrophy by repressing antihypertrophic genes. Conclusions: Taken together, our findings demonstrate that G9a orchestrates critical epigenetic changes in cardiomyocytes in physiological and pathological conditions, thereby providing novel therapeutic avenues for cardiac pathologies associated with dysregulation of these mechanisms. Abstract : Supplemental Digital Content is available in the text.